Electron microscopic heteroduplex analysis of "killer" double-stranded RNA species from yeast. - Fried, H M (1978)
Wild-type and mutant double-stranded RNA (dsRNA) species from the yeast Saccharomyces cerevisiae were studied by electron microscopic heteroduplex mapping to determine the sequence relationships among the different RNA molecules. Three mutant dsRNAs, 1.5, 1.4, and 0.73 kilobase, were found to be derived by the same internal deletion of the wild-type (I83 kilobases) molecule. This deletion includes a wild-type (1.83 kilobases) molecule. This deletion includes a segment of about 200 base pairs that was estimated to be nearly 100% A+U. In addition, the sequences of the two larger mutant RNA species are tandem, direct duplications. One of the duplicated molecules appears to have a second internal deletion that occurred after the duplication. The mutant dsRNAs are functionally similar to the defective interfering virus particles of animal viruses--all of the mutant species prevent the propagation of the wild-type dsRNA when both are present in the same cell. The four dsRNAs share the same sequences at their termini, a finding that may suggest that these sequences are important for the replication of the dsRNAs.